2008
DOI: 10.1093/esr/jcn064
|View full text |Cite
|
Sign up to set email alerts
|

Welfare States, Labour Market Institutions and the Working Poor: A Comparative Analysis of 20 European Countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(48 citation statements)
references
References 22 publications
1
39
0
8
Order By: Relevance
“…We focus on the degrees of decommodification and regulation, strictness of employment protection, bargaining centralisation, and family policy orientation. Therefore, this study refers to measures that are treated as relevant in the aforementioned policy discourse and established as key macro variables for explaining economic micro-level outcomes (Brady et al 2010, Lohmann 2009, Baranowska and Gebel 2010. Table 1 compares Germany and the UK based on these measures.…”
Section: Labour Market Policy Framework In Germany and The Ukmentioning
confidence: 99%
See 2 more Smart Citations
“…We focus on the degrees of decommodification and regulation, strictness of employment protection, bargaining centralisation, and family policy orientation. Therefore, this study refers to measures that are treated as relevant in the aforementioned policy discourse and established as key macro variables for explaining economic micro-level outcomes (Brady et al 2010, Lohmann 2009, Baranowska and Gebel 2010. Table 1 compares Germany and the UK based on these measures.…”
Section: Labour Market Policy Framework In Germany and The Ukmentioning
confidence: 99%
“…The average net replacement rate during unemployment (OECD 2010) is used as indicator for the degree of decommodification (Lohmann 2009). This measure refers to the overall generosity of the welfare state with regard to unemployment benefits.…”
Section: Decommodificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, studies have shown that full-time work among women significantly lowers the risk of poverty (Halleröd et al 2006). Even among women with full-time work, however, the proportion of the 'working poor' has substantially increased in recent years (Lohmann 2009), indicating that an increase in female labour supply does not necessarily enhance social cohesion nor lead to the true socio-economic empowerment of women (Lim undated).…”
Section: Effects Of Labour Force Participationmentioning
confidence: 99%
“…Empirical research has shown that this process led to increasing rates of atypical employment, lowwage work, and in-work poverty (Lohmann, 2009;Andreß and Lohmann, 2008;Lucifora et al, 2005;OECD, 2011). Specifically, outsiders to the labour market have been shown to react very sensitively to processes of policy transformation.…”
Section: Introductionmentioning
confidence: 99%